Risk Factors for Pulmonary Tuberculosis in Diabetes Mellitus Patients - Cut Suwirda; Radhiah Zakaria; Nurjannah Nurjannah; Meutia Zahara; Hafnidar A. Rani (Indonesian Journal of Global Health Research, 2025)
Tuberculosis (TB) is a contagious infectious disease that causes major health problems globally. Indonesia is a country with a high burden of TB cases, with an incidence of 312 per 100,000 population. The number of suspected tuberculosis cases in Aceh in 2022 is 85,945 cases. Aceh Besar has the second highest number of tuberculosis cases, namely 3644 people. DM sufferers have uncontrolled glucose levels so they are at risk of developing TB. This research was conducted to analyze the risk factors for the incidence of tuberculosis in DM sufferers at the Aceh Besar. This research is a quantitative research approach case control study. The sample in this study was DM sufferers with a total sample of 104 people with a sample number of 52 people in each group. Sampling in research uses the technique of purposive sampling. Sample selection for the control group was carried out by selecting DM sufferers of the same gender as the case group. Data collection was carried out using questionnaires and data from examination results from community health centers. Data analysis used multiple logistic regression tests with a confidence level of 95%. The results of the study showed that factors associated with the incidence of pulmonary tuberculosis in diabetes mellitus sufferers in Aceh Besar were secondary education (OR=8.84; 95%CI=1.67–46.69), not working (OR=3.12; 95%CI=1.16–8.35), poor lifestyle (OR=4.97; 95%CI=1.68–14.71), underweight nutritional status (OR=4.38; 95%CI=1.14–16.77), smoking (OR=3.19; 95%CI=1.35–7,55), unhealthy house (OR=2.36; 95%CI=1.07 – 5.18), poor quality of health services (OR=0.03; 95%CI=0.01–0.09), family history of TB (OR=9.40; 95%CI=2.57–34.34) and contact directly with TB sufferers (OR=4.71; 95%CI=1.79–12.40). The most dominant factor associated with the incidence of tuberculosis in diabetes mellitus sufferers in Aceh Besar is smoking (OR=12.71; 95%CI=2.07–77.68). It is hoped that the public, especially DM sufferers, will stop smoking to engage in physical activity or consider seeking support or health consultation to help stop smoking. Additionally, it is hoped to not have direct contact with TB sufferers, to and use a mask when interacting with TB sufferers.